Wheat Germ Agglutinin as a Potential Therapeutic Agent for Leukemia - Ryva, Bradley; Zhang, Keman; Asthana, Abhishek; Wong, Derek; Vicioso, Yorleny; Parameswaran, Reshmi (Frontiers in Oncology, 2019)
Dietary lectins are carbohydrate-binding proteins found in food sources. We used a panel of seven dietary lectins to analyze cytotoxicity against hematological cancers. Wheat germ agglutinin (WGA), even at low doses, demonstrated maximum toxicity toward acute myeloid leukemia (AML) cells. Using AML cell lines, we show time- and dose-dependent killing by WGA. We also show that low doses of WGA kills primary patient AML cells, irrespective of subtype, with no significant toxicity to normal cells. WGA caused AML cell agglutination, but failed to agglutinate RBC's at this dose. WGA, primarily, binds to N-acetyl-D-glucosamine (GlcNAc) and is also reported to interact with sialic-acid-containing glycoconjugates and oligosaccharides. After neuraminidase pre-treatment, which catalyzes the hydrolysis of terminal sialic acid residues, AML cells were less sensitive to WGA-induced cell death. AML cells were also not sensitive to succinyl-WGA, which does not react with sialic acid. Incubation with LEL lectin, which recognizes GlcNAc or SNA, which binds preferentially to sialic acid attached to terminal galactose in α-2,6 and to a lesser degree α-2,3 linkage, did not alter AML cell viability. These data indicate that WGA-induced AML cell death is dependent on both GlcNAc binding and interaction with sialic acids. We did not observe any in vitro or in vivo toxicity of WGA toward normal cells at the concentrations tested. Finally, low doses of WGA injection demonstrated significant in vivo toxicity toward AML cells, using xenograft mouse model. Thus, WGA is a potential candidate for leukemia therapy.